ответ:
объяснение:
1.
(x+2)(x-3)(x-4) < 0
(-2) (3) (4)
x∈(-∞ -2) u (3 4)
2
(x+5)/(x-2)/(x-1)^2 > =0
[-5] (1) [2]
x∈(-∞ -5] u [2 +∞)
3
(2x+1)/(x-3) < =1
(2x+1)/(x-3) - 1< =0
(2x+1 - x + 3)/(x-3)< =0
(x+4)/(x-3)< =0
[-4] (3)
x∈[-4 3)
4
x/(x-4) + 5/(x-1) + 24/(x-1)(x-4) < =0
(x(x-1) + 5(x-4) + 24)/(x-1)(x-4) < =0
(x^2 - x + 5x - 20 + 24) /(x-1)(x-4) < =0
(x^2-4x+4)/(x-1)(x-4) < =0
(x-2)^2/(x-1)(x-4) < =0
(1) [2] (4)
x∈(1 4)
добро ! получи неограниченный доступ к миллионам подробных ответов
попробуй сегодня
надеюсь если сможешь отметь как лучший
P₂(a)=4а⁴+6а³-2а²+2а
P₃(a)=2а⁵+3а⁴-а³+а²
A) P ( a ) = P₁( a )-P₂( a )+P₃( a ) =
= (2а³ + 3а² - а + 1) - (4а⁴ + 6а³ - 2а² + 2а) + (2а⁵ + 3а⁴ - а³ + а²)=
= 2а³ + 3а² - а + 1 - 4а ⁴- 6а³ + 2а² - 2а + 2а⁵ + 3а⁴ - а³ + а²=
= 2а⁵ - а⁴ - 5а³ + 6а² - 3а +1
Б) P( a ) = P₁( a ) + P₂( a ) - P₃( a ) =
= (2а³ + 3а² - а + 1) + (4а⁴ + 6а³ - 2а² + 2а) - (2а⁵ + 3а⁴ - а³ + а²)=
= 2а³ + 3а² - а + 1 + 4а ⁴+ 6а³ - 2а² + 2а - 2а⁵ - 3а⁴ + а³ - а²=
= - 2а⁵ + а⁴ + 9а³ + а + 1